Systematic Literature Review on Cybersecurity Issues in the Smart Home Environment - Fauzi, Rofiq; Candra Wulan, Puspa Ira Dewi; Perdana, Danis Putra (Compiler, 2024)
Method A literature study was conducted to examine cyber security in Smart Homes, focusing on vulnerability assessment, privacy, threat mitigation, and policy regulations. Not only smartphones have advanced technology, but smarthomes or smart homes are a technological development that allows users to control functions such as security access, temperature, lighting and home theater remotely. This is the basis for the need for user-friendly cybersecurity measures, considering the rapid adoption of IoT devices in smart homes. This literature review highlights challenges related to inconsistent regulations and varying technology standards. Significant gaps exist in user awareness, device interoperability, data privacy, and security protocols. A multidisciplinary approach that brings together technology, policy, and social science stakeholders is recommended to build a secure, efficient, and privacy-preserving smart home ecosystem